ISO 9001 : 2000 : a workbook for services organizations (ISO GenevaCH, 2005)
Presents a set of questions, checklists and planning guides, to be used as a tool for streamlining the internal process of conformities to ISO 9001 : 2000 standard, by professional service organizations in developing countries.
Keywords: QUALITY STANDARDS